Rooted in Samurai: Kazuo Ishiguro’s Religious Interrogations - Amit Mondal (PostScriptum: An Interdisciplinary Journal of Literary Studies)
Taking religion as a powerful influence in the construction of individual identity and contextualising Kazuo Ishiguro’s complex views on religion, particularly his statement expressing caution about “labelling himself an atheist”, this paper looks into the novelist’s distinctive approach to religious identity, which defies the confines of established norms and doctrine. It argues a case of constructing Ishiguro’s religious identity in his connection with samurai ethos that makes him different from the people who follow Christianity, Buddhism, Shintoism, or any other established religion in the world. Samurai principles represent a class consciousness where there is a sense of martial virtues, loyalty, and complete self-discipline. Originating and practised in medieval Japan the samurai way of life was very influential in Japanese culture, devoid of any sort of religious impression with it during that time. Over time, the samurai way of life directly came under the influence of Buddhism, Shintoism, and mostly Christianity. Thus, it has flourished and continued with a religious connotation even in modern Japan. In Japanese culture, the modern variation of the samurai has come to be known as bushido. Born to a Japanese family and raised in Britain’s cultural milieu, Ishiguro appears to find his religious roots in the traditional samurai heritage. For Ishiguro, this is indeed an alternative approach of identifying himself as an atheist. In doing so, Ishiguro negotiates between his cultural backgrounds, characterised by Christian principles and the cultural ethos of bushido predominant in England and Japan, respectively. Therefore, this paper argues the case of compromise that Ishiguro seems to discover between his Japanese and European cultural backgrounds, specifically concerning the issue of his religious identity. In this context, Ishiguro’s negotiation of identity is portrayed as more than merely adopting a middle ground; rather it involves the case of finding an alternative path for identity construction.